Processes in Pathogenic Biocolloidal Contaminants Transport in Saturated and Unsaturated Porous Media: A Review - Sen, Tushar (Springer, 2011)
There are several classes of subsurface colloids, abiotic and biotic. Basically, small particles of inorganic, organic and pathogenic biocolloids variety exist in natural subsurface system. Transport of these pathogenic biocolloidal contaminants (Viruses, bacteria and protozoa) pose a great risk in water resources and have caused large outbreaks of waterborne diseases. Biocolloid transport processes through saturated and unsaturated porous media is of significant interest, from the perspective of protection of groundwater supplies from contamination, assessment of risk from pathogens in groundwater and for the design of better water treatment systems to remove biocolloids from drinking water supplies This paper has reviewed the large volume of work that has already been done and the progress that has been made towards understanding the various basic multi-processes to predicting the biocolloid transport in saturated and unsaturated porous media. There are several basic processes such as physical, chemical and biological processes which are important in biocolloid transport. The physical processes such as advection, dispersion, diffusion, straining and physical filtration, adsorption and biological processes such as growth/decay processes and include active adhesion/detachment, survival and chemotaxis are strongly affected on biocolloid transport in saturated and unsaturated porous media.The unsaturated zone may play an important role in protecting aquifers from biocolloidal contamination by retaining them in the solid phase during their transport through the zone. Finally, author here highlighted the future research direction based on his critical review on biocolloid transport in saturated and unsaturated porous media.